Bisphenol A is an exogenous toxin that promotes mitochondrial injury and death in tubular cells. Issue 3 (7th December 2017) - Bosch‐Panadero, Enrique; Mas, Sebastian; Civantos, Esther; Abaigar, Pedro; Camarero, Vanesa; Ruiz‐Priego, Alberto; Ortiz, Alberto; Egido, Jesus; González‐Parra, Emilio
Abstract: Background: Uremic toxins that accumulate in chronic kidney disease (CKD) contribute to CKD complications, such as CKD progression. Bisphenol A (BPA) is a ubiquitous environmental toxin, structurally related with p‐cresol, that accumulates in CKD. Our aim was to characterize the nephrotoxic potential of BPA. Specifically, we addressed BPA toxicity over energy‐demanding proximal tubular cells. Methods: Cell death and oxidative stress were evaluated by flow cytometry and confocal microscopy in HK‐2 human proximal tubular epithelial cells. Functional assays tested ATP, intracellular Ca 2+, mitochondrial function (tetramethylrhodamine methyl [TMRM]), oxygen consumption, Nrf2‐binding, MitoSOX, and NADPH oxidase activity. Gene expression was assessed by qRT‐PCR. Results: Following acute exposure (24 hours), proximal tubular cell viability was decreased by BPA concentrations ≥50 μM while a seven‐day exposure resulted in a progressive loss of cell viability at a nanomolar range. Within 24 hours, BPA promoted mitochondrial dysfunction leading to energy depletion and increased mitochondrial and cytoplasmic oxidative stress and apoptosis in a concentration‐dependent manner. An antioxidant response was observed manifested by nuclear Nrf2 translocation and increased expression of the Nrf2 target genes Heme oxygenase 1 (HO‐1) and NAD(P)H dehydrogenase [quinone] 1 (NQO‐1). Conclusions: This study demonstrates for the first time that BPA causes mitochondrial injury, oxidative stress and apoptotic death in tubular cells. These results characterize BPA as an exogenous toxin that, similar to uremic toxins, may contribute to CKD progression.